Next‐generation sequencing‐based RiboMethSeq protocol for analysis of tRNA 2′‐O‐methylation - Marchand, Virginie; Freund, Isabel; Dalpke, Alexander (Biomolecules, 2017)
Analysis of RNA modifications by traditional physico‐chemical approaches is labor intensive, requires substantial amounts of input material and only allows site‐by‐site measurements. The recent development of qualitative and quantitative approaches based on next‐generation sequencing (NGS) opens new perspectives for the analysis of various cellular RNA species. The Illumina sequencing‐based RiboMethSeq protocol was initially developed and successfully applied for mapping of ribosomal RNA (rRNA) 2′‐O‐methylations. This method also gives excellent results in the quantitative analysis of rRNA modifications in different species and under varying growth conditions. However, until now, RiboMethSeq was only employed for rRNA, and the whole sequencing and analysis pipeline was only adapted to this long and rather conserved RNA species. A deep understanding of RNA modification functions requires large and global analysis datasets for other important RNA species, namely for transfer RNAs (tRNAs), which are well known to contain a great variety of functionally‐important modified residues. Here, we evaluated the application of the RiboMethSeq protocol for the analysis of tRNA 2′‐O‐methylation in Escherichia coli and in Saccharomyces cerevisiae. After a careful optimization of the bioinformatic pipeline, RiboMethSeq proved to be suitable for relative quantification of methylation rates for known modified positions in different tRNA species.
Gesehen am 01.10.2018